Contractor performance assessment scale: two-stage EFA for public construction procurement - Ali Raza Khoso (Proceedings of the Institution of Civil Engineers - Management, Procurement and Law, 2026)
For public procurement, the evaluation of competent contractors is one of the most effective decisions, especially for construction project delivery. Although a plethora of studies have developed contractor evaluation criteria, a limited validated measurement scale currently assesses contractor performance based on empirically structured capability dimensions. The present study aims to develop and validate the contractor performance assessment scale (CPAS). This instrument is designed to measure practitioners’ perceived importance of contractor capability dimensions which are conceptually distinct from direct capability measurement or post-award performance outcomes. A total of 109 construction professionals in Pakistan were approached to collect data. The study employs a five-phase model: item analysis and screening, two-stage exploratory factor analysis (EFA), scale validation [including confirmatory factor analysis (CFA), Heterotrait-Monotrait (HTMT)-based discriminant validity], and higher-order dimensional analysis. The 16 first-order factors produced by the first-stage EFA from three theoretically defined sub-pools load onto four higher-order CPAS dimensions confirmed by both EFA and CFA (comparative fit index = 0.906; root mean square error of approximation = 0.074). HTMT ratios confirm discriminant validity across all factor pairs. The CPAS offers procurement practitioners an empirically sound, importance-weighted tool to evaluate contractors in developing countries. It operates by scoring candidates across four capability dimensions during pre-award tender evaluation to support transparent and evidence-based contractor shortlisting.